Fossil Picrodendroid Fruit from the Upper Danian of Nûgssuaq, West Greenland. - Koch, B. Eske (Meddelelser om Grønland, 1972)
Rosenkrantzia picrodendroides n.gen. et n.sp., based on 47 specimens of fossil fruit in very good preservation, is described. The fruit was a nut (or drupe), with a thick pericarp or primitive anatomy. It is l-locular, containing one fully developed seed; about half of the specimens also contain remnants of a second aborted seed. The seed is pendulous from an apical placenta, and has a long longitudinal raphe. Hilum is distal, chalaza basal. The original ovary can be reconstructed: l-locular with min. two ovules, pendulous from the distal placenta, anatropous. The fully developed seed consists mainly of two thick, interrolded cotyledons with no distinct endosperm. The taxonomical investigation includes a study or fruits or two or the recent Picrodendron species. A phylogenetic conclusion is advanced which supports the position of the Picrodendraceae in the order Juglandales. The taxonomic position of Rosenkrantzia appears to lie somewhere between the Cupuliferae (Quercus group) and Juglandales, or in palaeontological terms, between the Dryophyllum and Dewalquea groups.